He says, she says: Exploring patterns of spousal agreement in Bangladesh - Ambler, Kate; Doss, Cheryl R.; Kieran, Caitlin; Passarelli, Simone (International Food Policy Research Institute, 2017)
Participation in household decisions and control over assets are often used as indicators of bargaining power. Yet spouses do not necessarily provide the same answers to questions about these topics. We examine differences in spouses’ answers to questions regarding who participates in decisions about household activities, who owns assets, and who decides to purchase assets. Disagreement is substantial and systematic, with women more likely to report joint ownership or decision making and men more likely to report sole male ownership or decision making. Analysis of correlations between agreement and women’s well-being finds that agreement on joint decision making/ownership is generally positively associated with beneficial outcomes for women compared with agreement on sole male decision making/ownership. Cases of disagreement where women recognize their involvement but men do not are also positively associated with good outcomes for women, but often to a lesser extent than when men agree that women are involved.